2016
DOI: 10.1111/jai.13210
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight and length-length relationships of five fish species in the Atrai River, Dinajpur, Bangladesh

Abstract: Summary A total of 502 specimens were obtained during monthly samplings from July to December 2015, by fishermen using seine nets, gillnets and cast nets. Length–weight (LWRs) and length–length (LLRs) relationships were estimated for five fish species collected from the Atrai River in the northwestern region of Bangladesh. The values of slope (b) in LWRs (r2 > .913, p < .001) were determined as 2.899 for Aspidoparia jaya, 3.059 for Gagata cenia, 3.004 for Gagata youssoufi, 2.755 for Salmophasia bacaila, and 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
2
10
1
Order By: Relevance
“…).The b values for Salmostoma bacaila, Botia lohachata, Ompok pabda and Trichogaster lalius were found to be quite close to the findings ofBorah et al (2017);Gupta, Sarkar, Bhardwaj, and Pal (2011);Hossain et al (2012)andIslam and Mia (2016) respectively Ahmed, Hossain, and Ohtomi (2012). found that b value in C. cachius ranged from 2.42 in October to 3.55 in July from old Brahmaputra River, Bangladesh.…”
supporting
confidence: 73%
“…).The b values for Salmostoma bacaila, Botia lohachata, Ompok pabda and Trichogaster lalius were found to be quite close to the findings ofBorah et al (2017);Gupta, Sarkar, Bhardwaj, and Pal (2011);Hossain et al (2012)andIslam and Mia (2016) respectively Ahmed, Hossain, and Ohtomi (2012). found that b value in C. cachius ranged from 2.42 in October to 3.55 in July from old Brahmaputra River, Bangladesh.…”
supporting
confidence: 73%
“…The estimated b value for P. atherinoides was found to be higher compared to Hossain and Afroze (). The available studies (Islam & Mia, ; Muhammad, Iqbal, & Akhlaq, ; Nath et al., ) on the LWR of S. bacaila so far using the name Salmophasia bacaila , an unaccepted name according to (WoRMS, ), which is presenting in the present study as the accepted name Salmostoma bacaila (WoRMS, ). The estimated b value for S. bacaila was found to be higher as compared to all available studies.…”
Section: Discussionmentioning
confidence: 74%
“…Spearman rank correlation coefficient (rs) for condition factors (Fulton's condition factor and relative body weight) with lengths (cm) and body weights (g) of five fishes in the Atrai River, Dinajpur, Bangladesh due to geographical variation but are within the limits for G. cenia (5.50-6.65 cm, Chaki et al, 2013), S. bacaila (3.40-15.20 cm, Masud andSingh, 2015) and S. phulo (6.00-10.70 cm and 1.36-7.21 g, Siddik et al, 2016), respectively. As there is a first record on length and body weight of G. youssoufi in the Atrai River (Islam and Mia, 2016), so no comparison was possible against this value with the previous one. According to Barnham and Baxter (1998), a fish is meager and elongated with lean body (CF f = 1.0), sound health (CF f = 1.20) and healthy body (CF f = 1.40).…”
Section: Resultsmentioning
confidence: 99%
“…(Fulton, 1904) and relative body weight as BW r = (BW/aTL b ) × 100 (Froese, 2006). Where, BW is body weight (g), TL total length (cm) while a and b are regression parameters previously estimated from LWRs by Islam and Mia (2016). According to Froese (2006), form factor (a 3.0 ) was estimated through an equation as a 3.0 = 10…”
Section: Methodsmentioning
confidence: 99%